Effects of intraperitoneal vitamin E, melatonin and aprotinin on leptin expression in the guinea pig eye during experimental uveitis - Kükner, A; Çolakoglu, N; Serin, D; Alagöz, G; Çelebi, S; Kükner, AS (Wiley, 2006)
Purpose: To observe ultrastructural changes and leptin expression in the guinea pig eye during experimental uveitis (EU) and the effects of vitamin E, melatonin and aprotinin on leptin expression. Methods: Thirty male guinea pigs were randomly classified into five groups. Group 1 was the control group. Groups 2, 3, 4 and 5 received intravitreal injections of bovine serum albumin (BSA) to induce EU. At the same time on the third day, groups 3 (EU + vitamin E), 4 (EU + melatonin) and 5 (EU + aprotinin) received intraperitoneal vitamin E (150 mg/kg), melatonin (10 mg/kg) and aprotinin (20 000 IU/kg), respectively. On the sixth day, histopathological and clinical scoring of inflammation were performed, and leptin expression was investigated in the retina, choroid, sclera, episclera and cornea, and compared. Result: There was a remarkable increase in leptin expression in the retina, choroid, sclera and episclera in the EU group. Leptin expression in the treatment groups was similar to that in the control group. At light and electron microscopic levels, ganglion cells were oedematous and inner plexiform layer thickness had increased in the EU group retinas. Oedema was decreased in the treatment groups. Comparison of the EU and treatment groups revealed significant differences histopathologically and clinically. Conclusion: Experimental uveitis causes an increase in leptin expression in the retina, choroid, sclera and episclera of guinea pigs. Vitamin E, melatonin and aprotinin inhibit this increase. Leptin seems to be closely related to ocular inflammation.
Keywords: experimental uveitis; leptin; vitamin E; aprotinin; melatonin